Identification of the Chemical Constituents of the Selected Fraction of the Dichloromethane Extract of Syzygium samarangense Stem Bark Using LC-ESI-MS and Evaluation Its Potential as Antifungal Agent - Tukiran Tukiran; Suyatno Suyatno; Frisca Nadya Safitri (Universitas Gadjah Mada, 2021)
Several extracts of Syzygium species have been shown to inhibit the growth of some fungal microorganisms implicated in skin diseases, such as Candida albicans included S. samarangense. However, an antifungal test of C. Albicans on this plant's stem bark had not been reported. This study aimed to identify chemical constituents of the selected fraction from dichloromethane extracts of the stem bark of S. samarangense and determine the antifungal activity of the selected fraction at various concentrations on C. Albicans. The identification of the chemical constituent of the selected fraction has been performed by the LC-ESI-MS technique. An antifungal test of the selected fraction was carried out using the disk diffusion method. The samples used included the selected fraction with 5 variations of concentration (2.5; 2.0; 1.5; 1.0; and 0.5%), positive control (ketoconazole 1%), and negative control (DMSO). The results showed that the selected fraction has antifungal activity on C. Albicans. The results showed that the selected fraction contains four flavonoids: pinocembrin, uvangoletin, stercurensin, and aurentiacin. Due to antifungal activity on C. Albicans, it has moderate activity at a concentration of 2.5%, while concentrations of 2.0, 1.5, 1.0, and 0.5% have weak activity.